Efficacy of Chlorantraniliprole in Combination with Lambdacyhalothrin (Ampligo 150 ZC) Against the Leaf Folder, Cnaphalocrocis medinalis (Guenee) in Rice Field - Meena, R.; Kumar, K. (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2024)
Rice is a cereal grain and a member of the grass family (Poaceae). One of the challenges faced by rice farmers is the infestation of pests, including the leaf folder (Cnaphalocrocis medinalis). A field experiment was conducted to assess the bio-efficacy of Chlorantraniliprole 9.3 + Lambda cyhalothrin 4.6 ZC against the rice leaf folder Cnaphalocrocis medinalis during the kharif season of 2020 and rabi season of 2021. The treatments included Chlorantraniliprole 9.3 + Lambda cyhalothrin 4.6 ZC at rates of 150, 200, and 250 ml per ha, Chlorantraniliprole 18.5 SC at 150 ml per ha, Lambda cyhalothrin 4.9 CS at 250 ml per ha, and Fipronil 5 SC at 1500 ml per ha. Analysis of pooled data revealed that all treatments were effective in controlling leaf folder damage, leading to a significant increase in yield. Among the tested chemicals, Chlorantraniliprole 9.3 + Lambda cyhalothrin 4.6 ZC at 250 and 200 ml per ha exhibited the highest reduction in leaf folder population, followed by Chlorantraniliprole 9.3 + Lambda cyhalothrin 4.6 ZC at 150 ml per ha and Chlorantraniliprole 18.5 SC at 150 ml per ha.